2020
DOI: 10.3390/ijerph17041399
|View full text |Cite
|
Sign up to set email alerts
|

The Accumulation and Metabolism Characteristics of Rare Earth Elements in Sprague–Dawley Rats

Abstract: The current study aims to investigate the influence of five rare earth elements (REEs) (i.e., lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), and gadolinium (Gd)) on the growth of Sprague–Dawley (SD) rats, and to explore the accumulation characteristics of REEs in tissues and organs with different doses as well as the detoxification and elimination of high-dose REEs. Fifty healthy male SD rats (140~160 g) were randomly divided into five groups and four of them were given gavage of sodium citrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…To date, only a small number of studies in the literature have analyzed the doseresponse relationships between REE exposure and their concentrations in biological matrices in rats. A previous study found that the concentrations of five REEs (La, Ce, Pr, Nd, and Gd) in rat fur were positively correlated with their administration dose [24], whereas no such correlation was found in whole blood, which is consistent with our findings. However, our study provides additional confirmation of the utility of up to 14 REEs as biomarkers.…”
Section: Discussionsupporting
confidence: 92%
“…To date, only a small number of studies in the literature have analyzed the doseresponse relationships between REE exposure and their concentrations in biological matrices in rats. A previous study found that the concentrations of five REEs (La, Ce, Pr, Nd, and Gd) in rat fur were positively correlated with their administration dose [24], whereas no such correlation was found in whole blood, which is consistent with our findings. However, our study provides additional confirmation of the utility of up to 14 REEs as biomarkers.…”
Section: Discussionsupporting
confidence: 92%
“…Fang et al (2018) found a significant effect on body weight and feed intake at 6 times higher concentration, or 60 mg La per kg body weight. However, Cao et al (2020) found no effect after a shorter 28-day exposure to 129 mg/kg body weight by gavage but a clear effect at the ten-fold concentration. This shorter exposure should be less representative of continuous exposures than the 90-day exposures of Fang et al (2018).…”
Section: A324 Mammalsmentioning
confidence: 76%
“…Scarce evidence suggests that a large fraction is lost from 5 to 8 weeks after ingestion for rats (Cao et al, 2020). A general retention time of 45 days was given by Nakamura, Tsumura, Tonogai, Shibata, and Ito (1997).…”
mentioning
confidence: 99%
“…REEs are commonly used in agriculture as forage additives and fertilizers and are consumed via the food chain. Approximately 90% of the global REEs are distributed in China, indicating more absorption hazards for the Chinese population ( 9 ). Although few studies focus on REEs, several studies still prompt that they might influence cancer.…”
Section: Introductionmentioning
confidence: 99%